2015
DOI: 10.1007/s00249-015-1078-x
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic analysis of decreased sperm fertilizing ability by fluorides and fluoroaluminates: a tool for analyzing the effect of environmental substances on biological events

Abstract: Fluorides and fluoroaluminates decrease mouse sperm fertilizing potential by modifying the process of sperm preparation for fertilization, so-called capacitation, followed by acrosome reaction (AR). Capacitation was monitored by protein tyrosine phosphorylation (pTyr), and AR was induced consequently. The aim of this study was to apply kinetic analysis to the previously obtained dependences of pTyr and AR at capacitation times, and propose a mathematical theory for a mechanism when sperm maturation ability is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Given that kinetic analysis has already been successfully used for analysis of data describing the reduced capacitation ability of sperm [36], it was also used to analyse the reaction of sperm with estradiol. The course of a sperm response on the added estradiol (Figure 1) indicated an autocatalytic character with a formation of an unstable adduct followed by its decomposition.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that kinetic analysis has already been successfully used for analysis of data describing the reduced capacitation ability of sperm [36], it was also used to analyse the reaction of sperm with estradiol. The course of a sperm response on the added estradiol (Figure 1) indicated an autocatalytic character with a formation of an unstable adduct followed by its decomposition.…”
Section: Resultsmentioning
confidence: 99%
“…The mathematical interpretations and general quantified process dynamics bring another perspective to help explain this crucial biological event. In a previous study [36], the mathematical theory for the mechanism when sperm maturation ability is amended by external stimuli [37] was proposed. It was shown that the chemical kinetics can be applied to sperm in the role of reactant and that kinetic analysis could be a useful tool for monitoring and predicting the specific molecular mechanisms involved in certain biological signalling pathways.…”
Section: Introductionmentioning
confidence: 99%
“…The method was greatly improved by using sensitive HPLC-MS/MS methods for monitoring the action of 17β-estradiol (E2) on the capacitation of mouse sperm in vitro, enabling monitoring of changes in hormone concentration levels during sperm capacitation even at the level of units of µg/L [25,26], thus approaching real values of potential exposure. The obtained results were subjected to kinetic analysis, which has been used successfully to study the mechanism of the action of fluorides and aluminum fluoride complexes on the capacitation ability of mouse sperm [27]. The results of kinetic analysis of concentration changes on the receptors of unbound E2 during time-dependent sperm capacitation have demonstrated that E2 is first adsorbed on the surface of plasmatic membranes and subsequently passes into the cytoplasm, where it forms an unstable adduct with the receptors; the formation of this adduct has an autocatalytic effect [26].…”
Section: Introductionmentioning
confidence: 99%